KAJIAN TEKNIS DAN EKONOMI PENGARUH PENGGUNAAN BAHAN BAKAR B-30 PADA MESIN INDUK KAPAL - Rarasaty Dwi Anoraganingrum Junaedi, (2022)
Diesel engines use biodiesel as fuel for engine combustion. One of the alternative fuels used for diesel engines is B-30. To determine the feasibility of B-30 fuel, technical testing of diesel engines is carried out on diesel fuel. The result obtained in the test on the Kipor 170F diesel engine that uses B-30 fuel and Diesel for Constant Rotation; the ratio of shaft power (kW) is 0,1279 (0,0942), 0,2898 (0,2195), 0,3463 (0,2837), 0,3974 (0,3514). For fuel consumtion (Kg/hour) of 0,3362 (0,3185), 0,3835 (0,3225), 0,4236 (0,3468), 0,4380 (0,3671). The thermal efisiency in % is 3,0096 (2,4384), 7,2966 (4,564), 8,0094 (6,0128), 8,3742 (6,9734). Meanwhile for Constant Load; in the ratio of shaft power (kW) of 0,3874 (0,3413), 0,9331 (0,4687), 1,3674 (0,5265), 1,8356 (0,5649). For fuel consumtion FC (Kg/hour) is 0,4268 90,2547), 0,7981 (0,5426), 1,2597 (0,9827), 1,5688 (1,2479). And the thermal efficiency (%) is 8,9036 (7,1894), 16,7135 (12,7212), 14,4887 (10,9825), 11,9436 (8,67894). Each for the use of diesel fuel and B-30. Keywords : B-30 fuel, Diesel fuel, shaft power ratio, fuel consumption, thermal efficiency.